1993
DOI: 10.1093/oxfordjournals.molbev.a040027
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Adh locus in the Drosophila willistoni group: the loss of an intron, and shift in codon usage.

Abstract: We report here the DNA sequence of the alcohol dehydrogenase gene (Adh) cloned from Drosophila willistoni. The three major findings are as follows: (1) Relative to all other Adh genes known from Drosophila, D. willistoni Adh has the last intron precisely deleted; PCR directly from total genomic DNA indicates that the deletion exists in all members of the willistoni group but not in any other group, including the closely related saltans group. Otherwise the structure and predicted protein are very similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Data from multiple species have found that the choice of synonymous codons can impact fitness, differing in the speed and accuracy with which they are read as a consequence of tRNA abundance and modification. In this regard, it is interesting that a dramatic shift in codon preference has been identified across the drosophilid lineage and in particular for the amino acids tyrosine, histidine, asparagine and aspartic acid [ 149 , 150 , 151 , 152 ]. For example, D. melanogaster show a preference for NAC codons whereas D. virilis has a preference for NAU codons [ 153 ].…”
Section: Queuosine In Translationmentioning
confidence: 99%
“…Data from multiple species have found that the choice of synonymous codons can impact fitness, differing in the speed and accuracy with which they are read as a consequence of tRNA abundance and modification. In this regard, it is interesting that a dramatic shift in codon preference has been identified across the drosophilid lineage and in particular for the amino acids tyrosine, histidine, asparagine and aspartic acid [ 149 , 150 , 151 , 152 ]. For example, D. melanogaster show a preference for NAC codons whereas D. virilis has a preference for NAU codons [ 153 ].…”
Section: Queuosine In Translationmentioning
confidence: 99%